Heritage and Archaeology: Responding to the Internationalisation Agenda in Postgraduate Teaching and Learning. (September 2015) - Chitty, Gill
Abstract : The internationalisation agenda is at the heart of most universities' strategic planning for growth. Beyond ambition for international recruitment, it attends to learning in preparation for life and work in a globalised society. Research indicates that internationalisation has been introduced into higher education in the UK with limited effect and little underpinning research into the internationalisation of the curriculum. This paper considers some of the pedagogical issues and literature raised by this agenda, reflecting on how archaeology and heritage studies might use this to advantage in its educational offer to a new 'internationalised' generation, to equip them for a globalised workplace. The Higher Education Academy's 2014 framework for internationalising higher education recognises the complex, wide-reaching, and long-term implications of this process. Archaeology and heritage studies have much to gain from embracing this agenda and enormous potential as an international learning environment, utilising pedagogies that situate learning in international and intercultural contexts and use constructive alignment to link learning, engagement, and assessment.